2014
DOI: 10.1084/jem.20131333
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional CD8+ T cells in hepatitis B and C are characterized by a lack of antigen-specific T-bet induction

Abstract: In humans infected with hepatitis B or C, high expression of a protein called T-bet in virus-fighting immune cells is associated with spontaneous clearance of the virus. Absence of T-bet was more often seen in patients whose infections became chronic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 47 publications
1
76
0
1
Order By: Relevance
“…Similarly, T-bet and Eomes were downregulated in antigen-specific CD8 T cells during chronic HCV-infection [37]. MAIT cells are distinct among T cells in that they express transcription factors for multiple effector programs including PLZF, T-bet, Eomes, and Helios, albeit some, including T-bet at low levels [8].…”
Section: Alterations In Mait Cell Transcription Factor Expression In mentioning
confidence: 96%
“…Similarly, T-bet and Eomes were downregulated in antigen-specific CD8 T cells during chronic HCV-infection [37]. MAIT cells are distinct among T cells in that they express transcription factors for multiple effector programs including PLZF, T-bet, Eomes, and Helios, albeit some, including T-bet at low levels [8].…”
Section: Alterations In Mait Cell Transcription Factor Expression In mentioning
confidence: 96%
“…Furthermore, IL-12 treatment combined with PD1 blockade further restores the function of exhausted HBV-specific CD8 + T cells in vitro 131 . A recent study showed that T-bet (also known as TBX21) expression is lacking in dysfunctional CD8 + T cells in chronic HCV infection and HBV infection and that exogenous IL-12 in addition to T-bet induction restores the cytokine production of these CD8 + T cells 132 .…”
Section: Chronic Hepatitis Virus Infectionmentioning
confidence: 99%
“…One possibility might be deletion of HBV-specific CD8+ T cells in patients with cHBV as supported by the finding of elevated expression of the proapoptotic molecule Bim 9. Nevertheless, it has been shown that the few detectable HBV-specific CD8+ T cells are functionally impaired, express several inhibitory receptors5 8 10–14 and display a dysregulation of the transcription factor T-bet 7. These findings are indicative of T cell exhaustion in cHBV infection.…”
Section: Introductionmentioning
confidence: 99%